Transthoracic Migration of a Foreign Body into the Diaphragm from the Gunshot Injury and Its Management in a Child: A Case Report - Dantis, Klein; Mehsare, Pranay Suresh; Singha, Subrata Kumar; Gupta, Nilesh (The Surgery Journal, 2022)
Intrapleural foreign bodies (FB) are rare and uncommon, while diaphragmatic FB secondary to gunshot injury in a child is still rarer. We now describe a 9-year-old male with a history of self-inflicted accidental air gun injury on the right side of the midline of the sternum with transthoracic migration of FB—lead bullet—measuring 1cm x1.4cm into the diaphragm managed initially with intercostal tube drainage for right hemopneumothorax at the different center underwent thoracoscopy followed by minithoracotomy and retrieval under C-arm guidance that has not been reported in the literature.
Keywords: hemopneumothorax; foreign body; diaphragm; C-arm; minithoracotomy